Bionic Construction of Helical Bi2O3 Microfibers for Highly Efficient CO2 Electroreduction. Issue 1 (22nd November 2022) - Ning, Hui; Wang, Yani; Fei, Xiang; Wang, Xiaoshan; Jin, Xin; Zou, Yecheng; Ma, Chang; Jiao, Zhenmei; Zhao, Yan; Wu, Mingbo
Abstract: Helical Bi2 O3 microfibers (HBM) were prepared with the assistance of cotton template through a simple heating treatment in air. This twisted structure induced the lattice strains, enriched the oxygen vacancies of Bi2 O3, and promoted the sufficient exposure of active sites simultaneously, thus performing outstanding activity and selectivity as catalyst for CO2 electroreduction to formate. The faradaic efficiency (FE) of formate reached 100.4±1.9 % at −0.90 V vs. reversible hydrogen electrode (RHE) in an H‐cell, and the partial current density was boosted to 226 mA cm −2 with FEformate of 96 % at −1.08 V vs. RHE in a flow cell. This work may open a new era for construction of metal oxide fibers by bionic strategy as high‐performance electrocatalysts. Abstract : CO2 electroreduction : Cotton is used as template to fabricate helical Bi2 O3 microfibers, which give outstanding performance as catalysts for CO2 electroreduction with a faradaic efficiency of 100.4±1.9 % towards formate at −0.90 V vs. reversible hydrogen electrode (RHE) and a large partial current density >200 mA cm −2 at a low potential of −1.08 V vs. RHE in a flow cell.